EFFECTIVENESS OF CMS-BASED LEARNING MEDIA ON STUDENT ENGAGEMENT AND LEARNING OUTCOMES IN VOCATIONAL HIGH SCHOOL OFFICE MANAGEMENT PROGRAMS BUSINESS SERVICES - Yuliantoro Wahyu Tirto Buono; Triesninda Pahlevi (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2025)
Phenomenon/Issue: The digital transformation in education has underscored the need for innovative learning strategies that enhance student engagement and academic achievement, particularly in vocational high schools (SMKs). However, many existing learning media remain insufficiently interactive and fail to foster active student participation. Purpose: This study aims to develop a Content Management System (CMS)-based learning media and evaluate its effectiveness in improving student engagement and learning outcomes in the Office Management and Business Services program at SMK. Novelty: The novelty of this research lies in the implementation of an interactive blog-based CMS tailored specifically for archival studies, integrating instructional videos, quizzes, and comment sections to promote independent exploration and active learning. Research Methods: The study employed a Research and Development (R&D) method using the ADDIE model and involved 11th-grade students at SMKN 1 Surabaya as research participants. Effectiveness was assessed through expert validation, classroom observations, pre-test and post-test evaluations, and student response questionnaires. Results: The results indicated that the CMS-based media was rated as highly feasible by expert validators. Empirical findings showed a significant increase in student engagement, demonstrated through active participation in discussions, task completion, and self-directed exploration of materials. Learning outcomes also improved significantly following the use of the CMS-based media. Research Contributions: This study contributes to the development of practical and effective digital learning media in vocational education and serves as a strategic reference for implementing technology-based instruction in vocational high school contexts